Estimation of samarium in nuclear fuel reprocessing streams by fiber optic aided spectrophotometry - Ganesh, S; K.Pandey, N. (International Journal of Advanced Chemistry, 2019)
A simple analytical procedure is developed and validated for the estimation of traces amount of samarium in aqueous streams of nuclear waste. In this method, the formation of chelation of samarium ion with 3, 6-bis [(2-Arsonophenyl) azo]-4,5dihydroxy-2,7-naphtalene disulphonic acid (Arsenazo III) to produce a reddish purple colour complex which has maximum absorption at 654 nm at pH 2.6-2.8. The intensity of the colour is proportional to the amount of Sm(III). Linear calibration graphs were obtained for 0.31 to 2.78 Âµg/mL of Sm(III) with a relative standard deviation (RSD) of 1.32 % and correlation coefficient of R2 = 0.999 (n=10). Its molar absorptivity and Sandellâ€™s sensitivity are found to be 4.88x104 L.Mol-1.cm-1 and 2.05x10-5 Âµg/cm2 respectively. The stoichiometric composition of the chelate is 1:1. The reaction is instantaneous, and absorbance remains stable for over 24 hrs. The system allowed for the determination of samarium with a limit of detection (LOD) (3.3Ïƒ/S) of 0.314 Âµg/mL, the limit of quantitation (LOQ) (10Ïƒ/S) of 0.952 Âµg/mL. A systematic study of the influence of different parameters like pH, the concentration of the complexing agent, the stability of the colour, the volume of the buffer and interference of other competing metal ions. Results of the present method are in good agreement with those obtained by the standard procedure. It is directly applicable for the determination of samarium in environmental, industrial, water and waste streams of the nuclear plant.Â Â